Profil Senyawa Bioaktif Berdasarkan Analisis GC-MS dan Aktivitas Antifungi Fraksi Asap Cair Kayu Mundu (Garcinia dulcis) terhadap Aspergillus flavus - Raka Wibawa Saputra; Dina Mulia Sari (Insight of Biology, 2026)
Aspergillus flavus is a major contaminant fungus of food commodities that produces aflatoxin B1, a highly potent carcinogenic compound that poses serious risks to food safety. The increasing resistance of A. flavus to synthetic antifungal agents has encouraged the exploration of natural alternatives, one of which is liquid smoke derived from mundu wood (Garcinia dulcis). This study aimed to identify the bioactive compounds present in three fractions of mundu wood liquid smoke using Gas Chromatography-Mass Spectrometry (GC-MS), evaluate the antifungal activity of each fraction against A. flavus, and determine the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC). Liquid smoke was produced through the pyrolysis of mundu wood at temperatures ranging from 350–400°C and subsequently fractionated sequentially using hexane, ethyl acetate, and water as solvents. GC-MS analysis identified 12 major bioactive compounds, with guaiacol (18.67%) as the dominant component in the ethyl acetate fraction and acetic acid (21.54%) as the major compound in the aqueous fraction. Antifungal activity assessed using the disk diffusion method showed that the 15% ethyl acetate fraction produced the largest inhibition zone (15.6 ± 0.26 mm), categorized as strong antifungal activity, with an MIC value of 2% (v/v). All fractions exhibited fungistatic properties. The ethyl acetate fraction of mundu wood liquid smoke demonstrated promising potential as a natural antifungal agent against A. flavus.